Aplikasi Penerjemah Kata Bahasa Inggris Ke Bahasa Indonesia Berbasis Kamera - Anang Kukuh Adisusilo (Informatics Engineering Department-UWKS, 2021)
The information is presented in an English At a place, could become a barrier to the review Human Understanding For A If the information does not understand the language. To translate a word of English to Bahasa Indonesia in the previous Nowadays of course ALL of the orangutans can do it anytime and anywhere by using a dictionary printed and digital dictionaries. If using a print dictionary Its thickness and weight, the user Must for One by One word from a few Page Up said Yang was found desirable. When using a digital input dictionary word Still Must BE user typed letter-by-letter. Research by THEREFORE hearts husband, author aims Building Applications translator of English words to Bahasa Indonesia-based camera that can translate English words picture from capturing Indonesian TO THE way. Husband developed the application on Android based smartphone device method uses OCR (Optical Character Recognition) detection engine AS Character And utilizing online translators AS machine translator. Testing of the findings for review TIN success rate translates said to reach 60% of the total of 30 samples tested Yang, so it can be deduced CAN Application That translates said destination language WITH KE hearts percentage of success of 60%. Inaccuracy of the findings due to the translation of image processing results That sometimes still give results the Less Net notably ON threshold and morphological processes (erosion and dilation).